Two new species of the genus Turbicellepora Ryland, 1963 (Bryozoa: Celleporidae) found on Lophelia coral from the Greenland slope - Denisenko, Nina V. (Zootaxa, 2016)
The genus Turbicellepora was established by Ryland (1963) in the course of his work on the Norwegian bryozoan fauna. At present, the genus includes 71 recent and fossil species, which have been reported from all continents and seas (Bock & Gordon 2014). The distinctive characteristics of the genus include a multiporous ooecium, proximal orificial sinus, an asymmetrically placed peristomial avicularium and enlarged or vicarious avicularia (Ryland 1963). Occasionally, an additional pre-oral avicularium is also present (Hayward 1978). Colonies have a changeable form. They can be massive and branching or have the form of a mound or flat crust. The most comprehensive comparative study of European species of the genus, with detailed descriptions of 13 taxa, was carried out by Hayward (1978), who noted that the genus seemed to be centred in the Atlanto–Mediterranean region.